Diagnosing Malnutrition In Toddlers Using The Dempster Shafer Method - Wulandari, Heny; Manurung, Hotler; Rahmadani, Suci (International Journal of Informatics, Economics, Management and Science, 2024)
Indonesia was the 5th most malnourished country in the world in 2012. The number of malnourished children under five is currently around 900,000, which is 4.5% of the total number of children under five in Indonesia. Malnutrition can have an impact on children's growth and health, even potentially causing death if not treated properly. Toddler nutrition can be seen from the food consumed and nutritional status by calculating anthropometric indicators based on age, gender, weight and height. The Dempster Shafer method is one of the expert system methods used to calculate probabilities. This method is used to calculate the data input made by the patient to get the percentage of accuracy of the diagnosis results. Based on research, the Dempster Shafer method can produce accurate data. This developed system aims to help provide clear information for patients or the general public and for medical personnel is expected to help in handling it provide the right solution, by only paying attention to the symptoms experienced .